2020
DOI: 10.1590/1807-3107bor-2020.vol34.0087
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation patterns of immune response-related genes in inflammatory external root resorption

Abstract: Inflammatory external root resorption (IERR) is a pathological process defined by the progressive loss of dental hard tissue, dentin, and cementum, resulting from the combination of the loss of external root protective apparatus and root canal infection. It has been suggested that healing patterns after tooth replantation may be influenced by the genetic and immunological profiles of the patients. The purpose of the present investigation was to evaluate the DNA methylation patterns of 22 immune response-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Many of them are also correlated with immune response [119][120][121][122][123][124]. In addition, ERR is also correlated with epigenetic machinery of some immune response-related genes [125]. Existing research has demonstrated that FOXP3 promoters in teeth experiencing ERR have higher levels of DNA methylation, which inhibits transcription factors from binding to their DNA binding sites, thus downregulate the expression of FOXP3.…”
Section: External Root Resorptionmentioning
confidence: 99%
“…Many of them are also correlated with immune response [119][120][121][122][123][124]. In addition, ERR is also correlated with epigenetic machinery of some immune response-related genes [125]. Existing research has demonstrated that FOXP3 promoters in teeth experiencing ERR have higher levels of DNA methylation, which inhibits transcription factors from binding to their DNA binding sites, thus downregulate the expression of FOXP3.…”
Section: External Root Resorptionmentioning
confidence: 99%